Pembelajaran Desain Grafis dan Pemrograman Dasar dengan Aplikasi Scratch untuk Siswa Ekstrakurikuler Komputer di SD Muhammadiyah 4 Surabaya - Pramono, Anang (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2024)
The development of digital technology in the current era has been enjoyed by all groups. From children to adults, they are part of the impact of technological development. Facing the challenges in this digital era, providing the right response to the nation's next generation is one of the important things that must be done .The hope is that our future generation will not just be technology enthusiasts but must be part of technological development, must become actors and be involved in technological development and must be implemented from an early age. Digital technology learning for elementary school children has become a serious concern, especially in urban areas. big cities in Indonesia. Elementary school students must be introduced to commuting and information technology from an early age. One of the things carried out in this community service activity is to provide learning, provision for students to have a basis in graphic design. Students are taught to make games, games with the SCRATCH application This application is considered suitable for children, because in this application students will be introduced to logic, basic understanding related to logic and programming language to produce design-based work. From the learning and training carried out, high enthusiasm and increased basic understanding for students regarding basics of design and programming